Concordance for Parkinson's disease in twins: A 20‐year update. Issue 4 (11th March 2019) - Goldman, Samuel M.; Marek, Kenneth; Ottman, Ruth; Meng, Cheryl; Comyns, Kathleen; Chan, Piu; Ma, Jinghong; Marras, Connie; Langston, J. William; Ross, G. Webster; Tanner, Caroline M.
Abstract : During the 1990s, we estimated the genetic contribution to Parkinson's disease risk in a large, population‐based twin registry. Because many unaffected twins were still alive, previous concordance estimates were based on incomplete information. Ninety‐five percent of twins are now deceased. Here, we update concordance and heritability through 2015 using National Death Index data. In total, we identified 30 concordant and 193 discordant pairs. Proband‐wise concordance was 0.20 in monozygotic and 0.13 in dizygotic pairs. Heritability was 0.27 overall, 0.83 in pairs diagnosed ≤50, and 0.19 in pairs diagnosed >50. High concordance in dizygotic twins suggests shared effects of early childhood environment. Ann Neurol 2019;85:600–605